Ion-Exchange Properties of Transcarpathian Natural Zeolites - V. Gomonaj; K. Szekeresh; P. Gomonaj; N. Golub (Adsorption Science & Technology)
The adsorption of ammonium ions, radionuclide ions (Sr 2+ and Cs + ) and heavy metal ions (Ni 2+ , Cr 3+ , Fe 3+ and Hg 2+ ) on natural Sokyrnytsky clinoptilolite has been investigated. Effective cation exchange of heavy metal ions and radioactive elements was observed with samples of the clinoptilolite which had been pretreated with ammonium chloride solutions. The adsorption isotherms for such cations from solutions of 0.5–1.0 mg/l ion content were studied under static conditions for adsorbent particle size fractions of 1.5–2.5 mm. Solid phases and solution aliquots were analyzed by X-ray fluorescence methods for Sr 2+ ions while the concentrations of other ions were analyzed by spectrophotometric methods.